(untitled) (Experimental biology, 2026)
In order to enhance plant resistance to biotic and abiotic stresses, an association of agronomically valuable microorganisms based on rhizospheric and endophytic bacteria was developed. The use of microbial associations is considered a more effective approach compared with monocultures, since microbial consortia possess a broader spectrum of biological activity and are capable of synergistic interactions within agroecosystems. For the formation of the association, the strains Pseudomonas flavescens D5, Serratia proteamaculans B5, and Pseudomonas fluorescens D7 were selected, characterized by plant growth-promoting and biocontrol properties. A comprehensive evaluation of the agronomically valuable properties of the association was carried out, including biosafety/biocompatibility, halotolerance, synthesis of indole-3-acetic acid, phosphate-mobilizing activity, and antifungal activity. It was found that the LYA23 association demonstrated increased IAA production compared with individual strains, reaching 63.4 μg/mL, pronounced phosphate-mobilizing activity (293 μg/mL), and maintained growth at NaCl concentrations up to 5%. The association exhibited high antagonistic activity against Fusarium graminearum and Fusarium oxysporum, forming growth inhibition zones up to 3.5 ± 0.1 cm. The polymer matrix composed of the biopolymers pullulan, pectin, and polyhydroxyalkanoate in a ratio of 2:1:0.1 was recognized as optimal for cell immobilization. The addition of potassium humate further enhanced the plant growth-promoting effect of the preparation. In vegetation experiments, treatment of barley seeds of the Arna cultivar increased germination up to 98.6% and significantly increased root and shoot biomass compared with the control.